Dropped appendicolith following an appendectomy - Mendoza Rojas, Hubert James (2023)
Dropped appendicolith following an appendectomy is a rare complication which may occur as a consequence ofappendicolith expulsion from the appendix due to a previous perforation or failure to identify the appendicolith. A fecalith generally becomes symptomatic over time, as a result of abscess formation, intestinal obstruction, fistula tract orinflammation of the appendiceal stump. Two cases of dropped appendicolith following an appendectomy are described hereinbelow. Case 1: A 23-year-old female patient, who underwent an appendectomy the previous day, was admitted to the emergency room due to hypogastric pain. A computed tomography (CT) scan revealed a dropped appendicolith in the right iliac fossa, and a diagnostic laparoscopy showed intra-abdominal abscesses and a dropped appendicolith in the appendicular stump. Case 2: A 77-year-old male patient, who underwent surgery for acute appendicitis caused by appendicoliths, showed abdominal distension on the sixth postoperative day. The CT scan revealed intestinal obstruction and a dropped appendicolith at bowel loops. In the surgical reintervention, erosion of the mesentery caused by the appendicolith was evidenced. Both patients progressed after the reoperations. The incidence of dropped appendicolith following an appendectomy is currently unknown since few data are available in the literature worldwide. Therefore, it is important to present these cases to expand the casuistry, learn more about dropped appendicoliths followingan appendectomy, demonstrate their complications if they are not removed early and show how to prevent them. Inconclusion, dropped appendicoliths following an appendectomy must be removed early to avoid complications.